Dissecting IPO Stock Price Dynamics: a Comparative Analysis of Short-Term and Long-Term Performance in the Indonesian Market: a Conceptual Paper - Alfarisy, Ghifary; Widodo, Arry; Silvianita, Anita; Rubiyanti, Nurafni (Formosa Journal of Applied Sciences, 2025)
The dynamics of short- and long-term share price performance in an Initial Public Offering (IPO) are of equal relevance for the understanding of issuers and investors. Typically, underpricing in early trading is driven by market and speculative behavior. Long-term stock performance is increasingly dependent on factors of a business nature, such as corporate management and profitability, as well as other intrinsic aspects of the issuing company. This study will conduct a comparative analysis using data collected from the Indonesia Stock Exchange in 2020-2023 in two different phases of performance characteristics. The results may provide insights into the implications of strategic decision-making in the IPO process as well as offer practical guidance for investment practices, making it easier for stakeholders to deal with the complexities of the IPO market.